Sharia Integration in Hospital Service: Implementation of Purity and Ikhtilāṭ Aspect - Muhammad Maksum; Afidah Wahyuni; Sahlul Fuad; Ade Rina; Farida Latifatul Hasanah; Fabien Bonhomme (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2022)
The application of sharia hospitals has implications for improving services. Two standards must be met, including purity and avoidance of ikhtilāṭ. However, this effort requires a large amount of money, affecting the principle of simple, fast and inexpensive service. The findings indicate that patients and their families benefit from adopting purity standards and avoiding ikhtilāṭ. Implementation of standard purity, however, does not fully have adequate management to ensure standard compliance. Meanwhile, implementing ikhtilāṭ avoidance standards is strongly influenced by the availability of resources and infrastructure. However, under certain conditions, the application of these standards is neglected. Implications This study emphasizes the need for detailed management and guidelines in applying these standards.